2008
DOI: 10.1097/hjh.0b013e3282fcc357
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the arginase inhibitor N ω-hydroxy-nor-L-arginine improves vascular function and lowers blood pressure in adult spontaneously hypertensive rat

Abstract: Pharmacological inhibition of arginase in adult spontaneously hypertensive rats decreases blood pressure and improves the reactivity of resistance vessels. These data represent in-vivo argument in favor of selective arginase inhibition as a new therapeutic strategy against hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 41 publications
8
70
2
Order By: Relevance
“…34,35 AHeFT suggested that chronic HISDN mediated positive effects on the myocardium. 17,23 NO exerts beneficial effects on the vasculature, 15,36 lowers SBP, 37 and also has direct effects on cardiac remodeling, 11 partly by increasing endothelial NO synthase and inhibiting LVH. [11][12][13] In our study, aldosterone induced LVH and diastolic HF, 18 and NO given in the form of ISDN was ineffective in reducing LVH or cardiomyocyte size despite SBP reduction.…”
Section: Hisdn and Cardiac Remodelingmentioning
confidence: 99%
“…34,35 AHeFT suggested that chronic HISDN mediated positive effects on the myocardium. 17,23 NO exerts beneficial effects on the vasculature, 15,36 lowers SBP, 37 and also has direct effects on cardiac remodeling, 11 partly by increasing endothelial NO synthase and inhibiting LVH. [11][12][13] In our study, aldosterone induced LVH and diastolic HF, 18 and NO given in the form of ISDN was ineffective in reducing LVH or cardiomyocyte size despite SBP reduction.…”
Section: Hisdn and Cardiac Remodelingmentioning
confidence: 99%
“…In accordance with this hypothesis, we recently showed that in vivo pharmacological blockade of arginase decreased endothelial dysfunction and prevented blood pressure rising in prehypertensive spontaneously hypertensive rats (SHRs) and young adult SHRs. 10,12 These latter studies only focused interest on the role of arginase in aortic and mesenteric endothelial dysfunction in SHRs, and as yet no study investigated the arginase pathway in tissues that encompass those implicated in the pathogenesis and pathophysiology of genetic hypertension, such as the heart, brain and kidney. However, hypertension-related damage to these target organs is a major cause of morbidity and mortality, and future antihypertensive therapy is expected to prevent or reduce it.…”
Section: Introductionmentioning
confidence: 99%
“…Pre clinical trial in adult spontaneously hypertensive rats showed that Nor-NOHA decreases blood pressure and improves the reactivity of resistance vessels. 23 Small scale clinical trial showed that nor-NOHA infusion increased endothelium-dependent vasodilatation in patients with coronary artery disease and diabetes mellitus type 2. 24 Arginase inhibition test on four samples showed that highest inhibitory effect was on Melastoma malabathricum leaf extract.…”
Section: Figure 1: Melastoma Malabathricum Leavesmentioning
confidence: 99%